Vygotsky's Warning: General Science and the Need for Metalevel Research. (2nd April 2016) - Edwards, Mark G.
ABSTRACT: Over ninety years ago Lev Vygotsky warned of a growing crisis in psychology and social science research. Vygotsky's warning has been echoed on many occasions but his solution to the problem has not been widely acknowledged. He advocated for a form of meta-science which he called "general science", an integrative science that could connect and guide the development of specialised disciplines and schools of research. In this paper I explore the parallels between Vygotsky's general science and contemporary forms of meta-level research and discuss their relevance and implications for addressing global challenges.